Cooperatives, farmer producer organizations and start-ups for strengthening vegetable supply chain - Pandey, Saurabh and Mishra, Shubham (The Cooperator)
(3z(BLarge scale clusters for vegetable production will be developed closer to major consumption centers. Co-operatives, FPO sand start-ups will be promoted for vegetable supply chains including for collection, storage, and marketing(3y(B, announced Hon$1 (Bble union finance minister Nirmala Sitaraman in her budge speech this yearss